If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + x = 5(15x + 2) Reorder the terms: 10 + x = 5(2 + 15x) 10 + x = (2 * 5 + 15x * 5) 10 + x = (10 + 75x) Add '-10' to each side of the equation. 10 + -10 + x = 10 + -10 + 75x Combine like terms: 10 + -10 = 0 0 + x = 10 + -10 + 75x x = 10 + -10 + 75x Combine like terms: 10 + -10 = 0 x = 0 + 75x x = 75x Solving x = 75x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-75x' to each side of the equation. x + -75x = 75x + -75x Combine like terms: x + -75x = -74x -74x = 75x + -75x Combine like terms: 75x + -75x = 0 -74x = 0 Divide each side by '-74'. x = 0 Simplifying x = 0
| 10x=15x+5 | | 1/3=-3/5u-1/2 | | 9s-1/3=3/2/3 | | 13=-1/6TH | | x^2+9x-25=0 | | 7x+4-6x=15-20 | | -0.18t=5.2 | | 2x-5=3x-1.50 | | x^20-4x^18+3x-6whenx=2 | | 4a+10a+3=a+42 | | 3/2-8/1 | | 0=2x^4+7x^3+4x^2+2x-3 | | (3x+6)*(2x-4)=94 | | 12-8=a/11 | | 216n=2/3 | | (3x+6)x(2x-4)=94 | | 5n^2+10n-85=0 | | 4(x+7)=12(x-5)+8 | | -4K+7K=3+2K-3+K | | 2/3n=216 | | 2x+2=128 | | 75-5(x-1)=13(x-1) | | 12y/-7=113 | | 5(x+1)=60 | | ax-7=b(x+2)forx | | 7g+8g+8+4= | | 27u-56=133 | | (x^2+1)(x^3+2x)(x^2-64)=0 | | 11sinx+5=sinx | | 77=7(m+1) | | (13+5y)-(16y-10)= | | M/-3-12=-5 |